Implementation of Parent and Teacher Collaboration in Instilling Character Values in Early Childhood: A Case Study at KB Al Farah, Seri Kembang III Village - Loka, Novita; Annisak, Annisak (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
Collaboration between parents and teachers is very important in instilling personality traits in early childhood. Because currently, several things that parents are focusing on are children's character in an era of increasingly sophisticated technology. Meanwhile, early childhood is the best time to build children's character which will influence their behavior in the future. For this reason, this research aims to find out about the implementation of collaboration between parents and teachers in instilling children's character from an early age. This case study uses a qualitative descriptive method with an approach developed by Miles and Huberman, including the process of data reduction, data presentation, and conclusion. The location of this research was carried out at Kb Al-Farah, Seri Kembang III Village. With children aged 3-4 years. The research results show that collaboration between educators and parents is very important in shaping the disciplinary character of early childhood. The research results also show that open communication, regular meetings, team formation, providing positive reinforcement, and consistency in educational approaches are all important factors in shaping the disciplinary character of early childhood in Kb Al-Farah Seri Kembang III village.